The Need for Software Migration Systems - Robert ENYEDI (Informatică economică, 2006)
Software translation activities tend to decrease in efficiency as the number of supported source and target languages increase. This paper presents an improved approach by organizing translators into software migration systems. It also analyzes the impact of this approach on the efficiency in the dynamics of such systems.